2022
DOI: 10.1186/s12890-022-02073-0
|View full text |Cite
|
Sign up to set email alerts
|

Mixed venous oxygen tension is a crucial prognostic factor in pulmonary hypertension: a retrospective cohort study

Abstract: Background The prognostic value of mixed venous oxygen tension (PvO2) at pulmonary hypertension diagnosis treated with selective pulmonary vasodilators remains unclear. This study sought to investigate the association of PvO2 with long-term prognosis in pulmonary arterial hypertension (PAH) and medically treated chronic thromboembolic pulmonary hypertension (CTEPH) and to identify the distinct mechanisms influencing tissue hypoxia in patients with CTEPH or PAH. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…A low partial pressure of arterial blood carbon dioxide (PaCO2) may be a useful noninvasive prognostic factor since a reduced PaCO2 reflects hyperventilation to maintain the partial pressure of arterial blood oxygen (PaO2). Similar results were shown for hypoxemia upon diagnosis as well as during follow-up under PAH medication [ 28 , 29 , 30 ]. In a recent study, pro-atrial natriuretic peptide (pro-ANP) and high-sensitivity troponin T (hsTnT) were found to have a significant prognostic value in patients with PAH [ 31 ].…”
Section: Pah Prognostic Factorssupporting
confidence: 81%
See 1 more Smart Citation
“…A low partial pressure of arterial blood carbon dioxide (PaCO2) may be a useful noninvasive prognostic factor since a reduced PaCO2 reflects hyperventilation to maintain the partial pressure of arterial blood oxygen (PaO2). Similar results were shown for hypoxemia upon diagnosis as well as during follow-up under PAH medication [ 28 , 29 , 30 ]. In a recent study, pro-atrial natriuretic peptide (pro-ANP) and high-sensitivity troponin T (hsTnT) were found to have a significant prognostic value in patients with PAH [ 31 ].…”
Section: Pah Prognostic Factorssupporting
confidence: 81%
“…This formula demonstrates that the SvO2 is directly associated with the CO and the oxygen delivery according to each patient’s need. However, it raises concerns about potential errors in measurement [ 29 ]. In a group of 98 patients with a CTEPH or PH associated with a systemic disease, Higgenbotam et al demonstrated that SvO2 is a robust prognostic factor of survival [ 58 ].…”
Section: Pah Prognostic Factorsmentioning
confidence: 99%
“…30 Global tissue hypoxia can be identified by using PvO 2 and it may be used as a prognostic marker. 30 PvO 2 and SvO 2 are closely related via the oxygen dissociation curve, but when the curve is shifted to the left by hypothermia the SvO 2 will be higher for any given, PvO 2 15 indicating an increased reluctance to release oxygen from hemoglobin. While SvO 2 is a marker of the oxygen supply demand matching under normothermic conditions, it is the partial pressure of oxygen that provides the driving gradient for oxygen movement into the tissues.…”
Section: Discussionmentioning
confidence: 99%
“…If the partial pressure of oxygen at the end of tissue capillaries falls below a critical level, it will hinder the oxygen supply to the tissues in the vulnerable “lethal corner.” 30 Global tissue hypoxia can be identified by using falsenormalPtruev¯O2 and it may be used as a prognostic marker. 30 falsenormalPtruev¯O2 and falsenormalStruev¯O2 are closely related via the oxygen dissociation curve, but when the curve is shifted to the left by hypothermia the falsenormalStruev¯O2 will be higher for any given, falsenormalPtruev¯O2 15 indicating an increased reluctance to release oxygen from hemoglobin. While falsenormalStruev¯O2 is a marker of the oxygen supply demand matching under normothermic conditions, it is the partial pressure of oxygen that provides the driving gradient for oxygen movement into the tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the establishment of treatment algorithms and reduced mortality due to PAH, the number of patients in the intermediate- and high-risk groups remain high (risk stratification according to the European Society of Cardiology and European Respiratory Society guidelines) [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%